Children in Brunei Darussalam: their educational, legal and social protections - Young, Amy; Pg Norhazlin Pg Hj Muhammad,; Osman Bakar,; O’Leary, Patrick; Abdalla, Mohamad (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
The past two decades of academic work, have cemented the idea that childhood is a social construction. As such, how children are conceptualized, educated, protected and interacted with differs from society to society, given the values inherent in each social construction. Culture, history and geography all influence the daily lives of children, and the inherent protections that children are offered in each society. This paper examines child protection provisions embedded in Brunei Darussalam by critically reviewing the sparse literature available. While much academic work has been done on Brunei Darussalam’s political system and unique ideology, little has been written on the children of Brunei. Specifically, the focus taken is on the protections offered by the Bruneian legal and education systems, family and cultural institutions, and on Brunei’s international commitments to ensuring child wellbeing.